The influence of language of instruction in the facilitation of academic activities: Nurse educators' experiences - Gugu Ndawo (AOSIS, 2019)
Background: Learners in most South African higher education institutions are taught mainly through English for most of their academic lives, yet many of them enter these institutions with poor proficiency in this language of instruction (LOI). Aims: The purpose of this article was to describe the experiences of nurse educators teaching in a 4-year comprehensive nursing diploma programme regarding the use of English as the LOI during academic activities. Setting: The nursing college under study offers a 4-year comprehensive nursing diploma programme as well as post-basic diploma qualifications such as Primary Health and Midwifery Nursing Science and is situated in Gauteng, South Africa. Methods: Twenty nurse educators were purposively sampled for in-depth individual interviews until data saturation and were requested to participate in the study. Tesch's protocol of qualitative data analysis was used and the themes that emerged were confirmed by an independent coder. Trustworthiness was ensured, and ethical considerations were adhered to. Results: It emerged that English language incompetence (1) undermines learners' self-esteem; (2) hinders critical, reflective and creative thinking; (3) renders understanding difficult and that (4) nurse educators' incompetence in LOI hinders meaningful teaching. Conclusions: Recommendations were made to improve the use of the LOI because through language interdisciplinary knowledge and understanding are integrated, thus ultimately providing patients with comprehensive, holistic and transcultural healthcare.